Development of a DIVA ELISA for diagnosis of Aujeszky's disease using recombinant gE fused to thioredoxin as antigen. (March 2020) - Silva-Junior, Luiz C.; Fontes, Karin F.L.P.; Nascimento, Sérgio A.; Rodriguez, Maria C.; Camargos, Marcelo F.; Freitas, Antonio C.; Castro, Roberto S.; Jesus, André L.S.
Highlights: Aujeszky's Disease (AD) virus gE protein fused to thioredoxin was produced in Escherichia coli . Thioredoxin-recombinant gE (Trx-gErec) fusion protein was used as coating antigen in the development of an ELISA. The ELISA could distinguish infected animals from vaccinated animals (DIVA). ELISAgErec showed high diagnostic sensitivity and specificity. ELISAgErec may also be used as a screening test in endemic and free areas of AD. Abstract: The major control methods for Aujeszky's Disease (AD) involve SHV1 gE gene-deleted vaccines and ELISA for detection of specific gE antibodies in infected animals, distinguishing infected animals from vaccinated animals (DIVA). This work aimed to develop a DIVA ELISA recombinant gE (gErec) for AD diagnosis using recombinant gE fused to thioredoxin protein. The analytical sensitivity and specificity were assessed with World Organisation for Animal Health (OIE) AD serum and sera from specific pathogen free (SPF), vaccinated SPF and AD-vaccinated SPF animals. The OIE serum reacted up to the recommended limit of detection and the other sera presented negative results. The cut-off point, diagnostic sensitivity and diagnostic specificity were determined by receiver operating curve analysis. This cut-off value corresponded to a diagnostic sensitivity of 97.60% and diagnostic specificity of 96.42%. Furthermore, two other cut-off points were chosen to discuss the ELISAgErec as a screening test in AD-endemic and free areas.